80. EEG is a time-dependent reliable indicator of good or poor outcome in comatose patients after cardiac arrest. Issue 4 (April 2016) - Spalletti, M.; Carrai, R.; Grippo, A.; Scarpino, M.; Ammannati, A.; Cassardo, A.; Peris, A.; Valente, S.; Amantini, A.
Abstract : The prognostic role of EEG during early phase after cardiac arrest (CA) has been recently emphasized, but different classifications and definitions have been employed among studies. A standardized terminology for ICU patients has been recently proposed by American Clinical Neurophysiology Society (ACNS). We retrospectively evaluated the prognostic value of EEG according to different times of recording in postanoxic comatose patients, classifying EEGs according to the ACNS terminology with a main focus on background continuity. The study included EEG of 211 patients, recorded at 12, 24, 48 and 72 h. At each timing we observed at least one EEG pattern with specificity of 100% for poor or good outcome. At 12 h "continuous" and "nearly continuous" EEGs were always associated to good outcome, whereas isoelectric EEG and "burst-suppression with highly epileptiform discharges" were always associated to poor outcome. At 24 h isoelectric and all "burst-suppression" EEGs were always associated to poor outcome. At 48 h and 72 h isoelectric, "burst-suppression" and "suppressed" (<10 μV) EEGs were always associated to poor outcome. Using a standardized classification, EEG provides time-dependent reliable indicators of good or poor outcome.